Epstein–Barr virus induces aberrant B cell migration and diapedesis via FAK-dependent chemotaxis pathways - Susanne Delecluse; Francesco Baccianti; Manon Zala; Alina Steffens; Carolin Drenda; Daniel Judt; Tim Holland-Letz; Remy Poirey; Pierre Sujobert; Henri-Jacques Delecluse (Nature Communications)
Abstract Infection with the Epstein-Barr virus (EBV) is a major risk factor for the development of cancer and autoimmune disorders. The virus enters the body in the pharynx, but EBV causes disease in distant organs, including the gut and the brain. Here we show, using in vitro culture and mouse infection models, that EBV-infected B cells display features of homing cells. Infected B cells undergo migration following paracrine CCL4 release and CCR1 induction, while CCR1 deficiency inhibits migration and, unexpectedly, proliferation of infected B cells. Furthermore, migrating EBV-infected B cells undergo CCL4-dependent diapedesis, induce ICAM-1 on endothelial cells, and disrupt the integrity of endothelial barriers. Both migration and diapedesis are regulated by FAK, with FAK inhibition blocking growth and survival of EBV-transformed B cells, as well as their spreading to spleen and brain in an animal model in vivo. Moreover, IL-10 secreted by EBV-infected B cells attracts and facilitates diapedesis of EBV-negative CD52highCD11c+ B cells, which have reported autoimmune properties. Our results thus provide mechanistic insight on EBV-induced B cell dysregulation, and also hint curbing migration as a potential target for reducing the pathogenicity of EBV-infected B cells.